Trzy zwiędłe liście, trzy smutne wiersze (Garczyński, Lenartowicz, Asnyk) - Hamerski, Wojciech (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
This text provides an interpretation of three poems, written by nineteenth century poets, that share a common theme of Autumn, with a particular attention given to the motif of a withered leaf. The author is interested how the poems in question match the elegiac convention of autumn lyric poetry and, at the same time, how each in its own way tries to overcome this convention. In Odpowiedź na list written by Stefan Garczyński, the acceptance of passing is concurrently met with defiance, expressed in a language of paradoxical metaphor. Teofil Lenartowicz in his Liście zwiędłe breaches the formal elegiac tone with the application of underlying vitalistic overtones included in the poem. Adam Asnyk’s Zwiędły listek, through a superposition of metonymies, achieves the effect of multilayered mediation and erasure of the trace of experience. The reading and understanding of the three poems, composed in Romanticism and post-Romanticism periods, make it possible to observe, fragmentarily of course, the multiplicity of different poetic attitudes that accompany the process of re-enchantment of the world.